Psycho-social risks at work: stress and coping strategies in oncology nurses (Revista Latino-Americana de Enfermagem, 2013)
OBJECTIVE: to identify sources of stress and coping strategies in nurses who work in three Head and Neck Surgery Oncology Services, in three central hospitals in Portugal. METHOD: a cross-sectional descriptive-exploratory study, whose sample was made up of the 96 nurses from the three services. The following were used in the data collection: a socio-demographic questionnaire; the 12-item General Health Questionnaire; and the Occupational Stress Inventory; Brief COPE. RESULTS: reasonable levels of general health were ascertained. The most-mentioned stressors were: burden with work; low pay; the physical space where they work; emotionally-disturbing situations and lack of recognition of the profession. The most-used coping strategies were: planning; active coping; acceptance and self-distraction. CONCLUSION: the stressors identified are mainly related to organizational aspects and work conditions, and the coping strategies chosen are aimed at resolving problems and improving the nurses' well-being. A significant percentage of the nurses presents high levels of pressure and depressed emotions. The results presented corroborate previous studies which warn of the importance of developing strategies for preventing these stress levels.